Human Leukocyte Transcriptome Changes in Response to Altered Gravity Environments: Investigations Using Bed Rest Participants and Astronauts Aboard the International Space Station - Stratis, Daniel (Université d'Ottawa / University of Ottawa, 2023)
Introduction: Space is an extreme environment exposing astronauts to microgravity and cosmic radiation resulting in immune dysfunction. To overcome the complex challenges of studying astronauts in space, bed rest studies represent an alternative model simulating microgravity exposure on Earth. We sought to characterize the steady state transcriptome changes in leukocytes isolated from two microgravity models: (1) participants to 60 days of bed rest and (2) astronauts to ~6 months of spaceflight. Methods: The bed rest study recruited twenty healthy men receiving a nutritional supplement or not; the spaceflight study had fourteen male and female astronauts participate. For both studies, ten blood samples were collected over three study phases, leukocytes were isolated, and transcriptomes were quantified using high throughput RNA-sequencing. My pipeline of data analysis applied differential expression (DE) methods and functional enrichment to identify gene expression changes and pathways responding to the altered gravity environments of both bed rest and spaceflight models. Results: Temporal differential expression identified transcriptome modulation reflecting multisystem shifts and immune dysregulation in response to the transitions to and from bed rest (2,415 DE genes) and spaceflight (247 DE genes). Interestingly, later bed rest and in-flight timepoints trended towards stable RNA levels with no differential expression. The bed rest study found the nutritional intervention had no mitigating effects on transcriptome changes (0 DE genes), and the spaceflight study revealed down-regulation in response to spaceflight followed by an opposite up-regulation upon return to Earth. Conclusion: The altered gravity environments of bed rest and spaceflight significantly modulated leukocyte transcriptome compositions revealing immune dysfunction at the molecular level. Future analyses utilizing the higher quality bed rest dataset is required to isolate the effect of microgravity from other space stressors and apply validation experiments to develop gene biomarkers indicative of immune deconditioning.
Keywords: Leukocytes; Transcriptome; Astronauts; Bed rest; Altered gravity; Immune genes